Ministernotomy: A preliminary experience in heart valve surgery - Kovačević Pavle; Mihajlović Bogoljub; Velicki Lazar; Redžek Aleksandar; Ivanović Vladimir; Komazec Nikola (Vojnosanitetski Pregled)
Background/Aim. The last decade of the 20th century brought up a significant development in the field of minimally invasive approaches to the valvular heart surgery. Potential benefits of this method are: good esthetic appearance, reduced pain, reduction of postoperative hemorrhage and incidence of surgical site infection, shorter postoperative intensive care units (ICU) period and overall in-hospital period. Partial upper median sternotomy currently presents as a state-of-the art method for minimally invasive surgery of cardiac valves. The aim of this study was to report on initial experience in application of this surgical method in the surgery of mitral and aortic valves. Methods. The study was designed and conducted in a prospective manner and included all the patients who underwent minimally invasive cardiac valve surgery through the partial upper median sternotomy during the period November 2008 - August 2009. We analyzed the data on mean age of patients, mean extubation time, mean postoperative drainage, mean duration of hospital stay, as well as on occurance of postoperative complications (postoperative bleeding, surgical site infection and cerebrovascular insult). Results. During the observed period, in the Institute for Cardiovascular Diseases of Vojvodina, Clinic for Cardiovascular Surgery, 17 ministernotomies were performed, with 14 aortic valve replacements (82.35%) and 3 mitral valve replacements (17.65%). Mean age of the patients was 60.78 ± 12.99 years (64.71% males, 35.29% females). Mean extubation time was 12.53 ± 8.87 hours with 23.5% of the patients extubated in less than 8 hours. Mean duration of hospital stay was 12.35 ± 10.17 days (in 29.4% of the patients less than 8 days). Mean postoperative drainage was 547.06 ± 335.2 mL. Postoperative complications included: bleeding (5.88%) and cerebrovascular insult (5.88%). One patient (5.88%) required conversion to full sternotomy. Conclusion. Partial upper median sternotomy represents the optimal surgical method for the interventions on the whole ascendant aorta (including aortic valve) and mitral valve through the roof of the left atrium, with a few significant advantages compared to the full sternotomy surgical approach.